Perceived social support as a mediator between coping and stress in first-year students during the COVID-19 Pandemic - Rahmanto, Septian Wahyu; Nuryanti, Lusi; Asyanti, Setia (Insight: Jurnal Ilmiah Psikologi, 2024)
The COVID-19 pandemic has impacted the education sector and caused stress for first-year students who have to adapt to a period of continence in higher education. Students can deal with stress using coping methods, but the coping mechanisms they choose may not always reduce stress. Coping strategies are not the only way to deal with stress; perceived social support also contribute to students’ stress levels. This study aims to determine the role of perceived social support as a mediator between coping and stress in first-year students during the COVID-19 pandemic. Using the cluster random sampling technique , 437 first-year students were selected, comprising 111 men and 326 women, as participants. The instruments for data collection were DASS-21, Brief COPE-28, and ISEL-16. The data were analyzed using the Sobel test technique. The indirect effect results show that perceived social support is a mediator between problem-focused coping (PFC) with stress (p < 0.001; β = -0.027), emotion-focused coping (EFC) with stress (p < 0.001; β = -0.020), and avoidant coping (AVC) with stress (p < 0.001; β = 0.035). Perceived social support has a full mediation effect on the relationship between PFC and stress, the relationship between EFC and stress, and a partial mediation effect on the relationship between AVC and stress. PFC and EFC will not be able to play a significant role in reducing stress levels if there is no perception of social support. This study provides findings that when first-year students use AVC, the environment needs to provide positive social support. Therefore, the role of AVC is reduced and stress levels are reduced. The findings of the mediating role of perceived social support are beneficial because they provide empirical evidence for theoretical and practical implications. Keyword: Stress, coping, perceived social support, COVID-19 Pandemic, isel-16